Chryseobacterium indologenes Keratitis: Successful Treatment of Multidrug-Resistant Strain. (11th May 2021) - Lee, Ivan J.; Mauger, Thomas
Abstract : A 72-year-old male with history of monocular vision with complete vision loss in his right eye from previous retinal detachment presented with 20/200 vision in the left eye with a corneal ulcer. Culture was obtained, and the patient was started on fortified tobramycin, fortified vancomycin, and amphotericin. Despite the antibiotics, the patient did not significantly improve, after which another culture was obtained before the patient was taken to the surgery for cryotherapy and a partial conjunctival flap. The culture identified Chryseobacterium indologenes . There have been fewer than a handful of cases reported in the last three decades with different antibiotic susceptibility profiles. Our patient was successfully treated with ciprofloxacin and ceftazidime with the final vision of 20/40.